A note of thanks (Epidemiology, Biostatistics, and Public Health, 2022)
The editors-in-chief, editors, members of the editorial board and publisher of Epidemiology, Biostatistics and Public Health wish to express their sincere gratitude to the referees of the articles considered for the 2013 volume of the Journal. Giuseppe ArbiaFabio BarboneJoana BastosStefania BocciaAnna BossiSilvio BrusaferroChiara CadedduCaterina CaminitiGiovanni CapelliGuido CitoniGianfranco DamianiAntonio De BelvisEmma De FeoElisabetta De VitoChiara de WaureDomitilla Di ThieneAna DuarteBruno FedericoMonica FerraroniAlessandra FrustaciCarlotta GaleoneSilvano GallusMaurizio GenuardiGuglielmo GiraldiMaria Rosaria GualanoCarolina IanualeFarhad IslamiGiuseppe La TorrePatrizia LaurentiLaura LauriaCarlo La VecchiaEmanuele LeonciniAlice MannocciWalter MazzuccoSilvia MiccoliCristina MontomoliEva NegriNicola NicolottiCaterina PalazzoGianCarlo ParadisiPatrizio PasqualettiClaudio PelucchiBrunella PosteraroDelphine PraudGianluigi QuarantaLuca SbrogiòBenedetto SimoneGiuliana SolinasMaria Lucia SpecchiaAnnamaria TortoranoFabio TuroneBrigid UnimMaria Assunta VenezianoFrancesco VitaleAntonella ZambonAlessandro Zanetti.